Design of Intelligent Gps Navigation System for Bus Monitoring and Station Reporting - Muhammad, Rauf; Abdalla, Ahmed N.; Nik M., Kamal; Azher, Fakharuddin (2009)
Nowadays, easily observe many peoples standing on the bus station in order to get their desired BUS but sometimes it take too much time for them to wait because many times there may be a traffic jam or some other problem with the Bus to reach at right at time. In this paper a new intelligent bus movement monitoring system and station reporting system based on GPS and RF Transceivers is presented. The neural networks is used to process raw, uncorrected signals received by GPS receiver, which is used to correct the raw signal and to obtain highly accurate position coordinate data. The neural network is trained with a particular GPS receiver. In addition to some fundamental functions such as real-time monitoring, some featured functions can tightly be combined to make the system compatible with the daily operations of any public transport scheme. The proposed method will surely improve the average accuracy of GPS signal reception at the bus station which led people to take decision either to wait for Bus or not.